Willingness-to-pay for COVID-19 vaccine in ten low-middle-income countries in Asia, Africa and South America: A cross-sectional study - Samsul Anwar; Amanda Yufika; Marhami Fahriani; Milda Husnah; Rawan Raad; Namareg ME. Khiri; Rashed YA. Abdalla; Rashed Y. Adam; Mohajer IH. Ismaeil; Asma Y. Ismail; Wajdi Kacem; Zeineb Teyeb; Khaoula Aloui; Montacer Hafsi; Nesrine Ben Hadj Dahman; Manel Ferjani; Dalia Deeb; Dina Emad; Farah S. Sami; Kirellos Said Abbas; Fatma A. Monib; Subramaniam R; Suhrud Panchawagh; Khan Sharun; Sunil Anandu; Mahir Gachabayov; Md A. Haque; Talha B. Emran; Guilherme W. Wendt; Lirane ED. Ferreto; María F. Castillo-Briones; Rocío B. Inostroza-Morales; Sebastián A. Lazcano-Díaz; José T. Ordóñez-Aburto; Jorge E. Troncoso-Rojas; Emmanuel O. Balogun; Akele R. Yomi; Abiodun Durosinmi; Esther N. Adejumo; Eyiuche D. Ezigbo; Morteza Arab-Zozani; Elham Babadi; Edris Kakemam; Irfan Ullah; Najma I. Malik; Deema Dababseh; Francesco Rosiello; Seyi S. Enitan; Malik Sallam; Hendrix I. Kusuma (Narra Sains Indonesia, 2022)
Vaccine hesitancy is considered as one of the greatest challenges to control the ongoing coronavirus disease 2019 (COVID-19) pandemic. A related challenge is the unwillingness of the general public to pay for vaccination. The objective of this study was to determine willingness-to-pay (WTP) for COVID-19 vaccine among individuals from ten low-middle-income countries (LMICs) in Asia, Africa, and South America. Data were collected using an online questionnaire distributed during February - May 2021 in ten LMICs (Bangladesh, Brazil, Chile, Egypt, India, Iran, Nigeria, Pakistan, Sudan, and Tunisia). The major response variable of in this study was WTP for a COVID-19 vaccine. The assessment of COVID-19 vaccine hesitancy was based on items adopted from the World Health Organization (WHO) Strategic Advisory Group of Experts (SAGE) vaccine hesitancy scale constructs. In this study, 1337 respondents included in the final analysis where the highest number of respondents was from India, while the lowest number was from Egypt. A total of 88.9% (1188/1337) respondents were willing to pay for the COVID-19 vaccination, and 11.1% (149/1337) were not. The average WTP for COVID-19 vaccination was 87.9 US dollars (), (range: 5-200). The multivariate model analysis showed that the country, monthly household income, having a history of respiratory disease, the agreement that routine vaccines recommended by health workers are beneficial and having received the flu vaccination within the previous 12 months were strongly associated with the WTP. Based on the country of origin, the highest mean WTP for COVID-19 vaccine was reported in Chile, while the lowest mean WTP for the vaccine was seen among the respondents from Sudan. The availability of free COVID-19 vaccination services appears as a top priority in the LMICs for successful control of the ongoing pandemic. This is particularly important for individuals of a lower socio-economic status. The effects of complacency regarding COVID-19 extends beyond vaccine hesitancy to involve less willingness to pay for COVID-19 vaccine and a lower value of WTP for the vaccine.